PENANAMAN NILAI-NILAI KARAKTER DALAM PEMBELAJARAN SENI BUDAYA (MUSIK) DI SMP NEGERI 22 PADANG - Vani Melda Zarlin; Jagar Lumbantoruan; Marzam Marzam (FBS Universitas Negeri Padang, 2018)
Abstract This article aimed to: 1) describe and analyze the cultivation of character values in the learning of art and culture (music), 2) obstacles faced by teachers, 3) the efforts of teachers in facing the constraints of the character values in the learning of Cultural Arts (Music). The type of the research was a qualitative research with descriptive method. The objects of research were the students of class VII-4 and art and culture teacher of SMP Negeri 22 Padang. Instruments in this study were researcher and assisted with supporting instruments such as stationeries and camera photo. Data collection techniques of this research were literature study, interview, observation and documentation. The results showed that embedded values of character in the learning of art and culture, especially music in class VII.4, and a good impact in music art learning. The statement was evidenced by students able to have the character of cooperating, disciplined, religious, curiosity, and confidence. These character values were inherent in the learning objectives in the cognitive, affective, and psychomotor domains. Keywords: Values of character, Learning, Cultural Art